Pharmacist-Doctor Collaboration Gaps & Diabetes Patient Quality of Life: Case study at Hospital X in Magelang - Cut Dewi Bunga; Elmiawati Latifah; Yasmine Noorindah Zulfani; Ariska Yulaikha; Bilqis Rahil Azizah; Perdana Priya Haresmita (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
ntroduction: According to data gathered from the Medical Records Unit of Hospital (RS) X in Magelang City for the year 2022, diabetes was the most prevalent condition, with a total of 2,866 recorded cases. To enhance treatment outcomes for patients, particularly those with chronic diseases, it is essential for physicians and pharmacists to collaborate effectively. Effective communication and collaboration among healthcare professionals, including physicians and pharmacists, are crucial to ensure seamless service delivery. This study aims to examine the gaps in collaboration among healthcare professionals—particularly between pharmacists and physicians—by exploring the current implementation of collaboration, identifying the challenges faced, and recommending strategies to optimize pharmacist-physician collaboration. Strengthening this collaboration may contribute to improving the quality of life of patients with diabetes. Methods: This study employs a qualitative approach, utilizing data collection methods such as interviews and focus group discussions, structured into seven distinct stages. The participants in this study include medical professionals, pharmacists, members of the pharmacy and therapeutics committees, hospital management personnel, and patients. Data analysis was conducted using explicitation techniques with the aid of the NVivo 12 software application, resulting in the identification of four key themes. Results: Through a qualitative approach, four main themes were identified. The first theme is the role of the Pharmacy and Therapeutics Committee, where the committee is responsible for drug selection, monitoring expired medications, compiling and distributing the hospital formulary, and providing appropriate therapy recommendations. The second theme is collaboration implementation, which is carried out through regular meetings, patient education, confirmation of drug availability and usage instructions, as well as coordination among healthcare professionals. The third theme is efforts to enhance collaboration, which include formulary updates, evaluation of drug needs, education for patients and medical personnel, and strengthening of standard operating procedures (SOPs) and interprofessional communication. The fourth theme is collaboration barriers, which include limitations in human resources, delayed communication, suboptimal evaluation of pharmaceutical personnel, and collaboration that is not yet fully integrated. Conclusion: The partnership between doctors and pharmacists at Hospital X in Magelang City in providing care for diabetes mellitus patients is in place but requires further optimization. To strengthen collaboration, the hospital can implement a structured interprofessional framework, including formal communication channels, cross-professional training, supportive internal policies, and active involvement of hospital management. These efforts are expected to enhance team effectiveness and improve the overall quality of patient care.